Evaluation of Prevalence Patterns of Dengue Fever in Lahore District through Geo-Spatial Techniques - Syed Ali Asad Naqvi,; Syed Jamil H. Kazmi,; Saima Shaikh ,; Maryum Akram, (Journal of Basic & Applied Sciences, 2015)
Dengue and its impacts are growing environmental, economic and health concerns in Lahore. Disease pattern is important to know for better control and effective management, GIS is one of the tested tools and quite efficient for this purpose. In this study, firstly month-wise dengue cases mapping for seven consecutive years (2007-2013) is performed in order to reveal temporal or seasonal pattern of dengue disease in Lahore district. Then a composite analysis was conducted using Inverse Distance Weighted (IDW) technique in order to show dengue most affected locations (towns) and in this analysis, all cases of the study period (2007-2013) were appended and visualized by IDW. Temporally, September (6548 cases) was the most dengue affected month of all years whereas February (4 cases) was marked as least affected throughout the dengue incidence period. Endemic Foci is noticed in 2011 most affected months. This cluster of disease is agglomerated near Ravi River and Densely Populated Towns, which further aggravated the incidence of dengue in economically deprived areas. Data Gunj Baksh town was the most affected town and IDW results showed that this town is composite endemic foci where cases were agglomerated most frequently. The reason of prevalence in this town would possibly be due to its more density of population and proximity of Ravi River.